Edukasi Gangguan Pendengaran Pada Pasien Poliklinik Di RSUD Praya - Yuliyani, Eka Arie; Prasetyaningrum, Ika; Yogiswara, I Made Arya; Annisa, Baiq Wanda; Setyawati, Shafira Dyah (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
One of the senses that plays a very important role in the hearing process is the ear. Disturbances in the hearing process can have a negative impact on a person's quality of life, including creating obstacles in communication and in some cases can cause anxiety, depression and even disruption of social interactions. Hearing loss in babies and children and teenagers will have a big impact on their daily lives, namely obstacles in children's social communication, cognitive development and emotions. This health education activity is a series of World Hearing Day events, where a campaign is carried out regarding the importance of maintaining healthy ears and hearing. The aim of this activity is to provide knowledge to the public about the importance of maintaining ear and hearing health and to urge the public to care more about ear and hearing health. The large public interest in this education can also be used as a benchmark for the success of transferring knowledge and information regarding the material presented and as input and evaluation material for similar activities in the future